(untitled) (Global Journal of Science Frontier Research, 2023)
Based on general systems theory in Optical Chaos Theory and aided by the Systems Engineering has developed an ecological model system for the environmental recovery treating the area as a complex dynamic system hypersensitive to initial conditions to prepare the ground Assuming that the degraded areas are hypersensitive to the initial conditions of soil preparation we applied the technique to trigger the roughness over time emergent properties that speed up the process of environmental recovery Was evaluated in the process of the evolution of environmental restoration components soil vegetation wildlife water and microclimate under the effect of roughness as auxiliary components in the internalization of matter and energy in the degraded area We compared the evolution of biotic and abiotic environmental variables in the model preparation of rugged terrain with the conventional model consisting of flat surfaces and more regular